Examining cash waqf and its usage: divergence from the waqif’s will as a use case - Ghalia, Bouhedda; Mohamad, Nor Asiah; Ali, Jawwad (The Islamia University Of Bahawalpur,IUB,Pakistan, 2023)
Immovable assets such as land and building, etc., are no more a common asset in creating a Waqf. At present, the practice has progressed from its traditional manner to an innovative method in which the specific purpose (Maqāṣid Khāṣṣah) of Waqf that benefit the Wāqif (endower) and subject matter of Waqf, and general purpose that benefit the society, could be attained easily and successfully. One of the methods repeatedly discussed and applied in contemporary times is the cash Waqf model. The model is a new form of Waqf presenting an innovative and effective tool for the practical delivery of its advantages according to the purpose of Waqf for which it is constituted. Its application in some situations has been perceived as confronting with a number of Sharī’ah and operational issues that need answers. The usage of cash Waqf against the Wāqif’s intention as presented in the Waqf deed or Sīghah is one of the issues that needs be addressed. Despite the significant role of cash Waqf in socio-economic development, there has been a substantial gap in the literature available due to continuous developments in the area which calls for more academic research. Thus, this study examines the usage of cash Waqf against the Wāqif’s will and its reasons. This study is qualitative, in which it employs library research skill as a method of research.